Word of Mouth Agen Judi Online dalam Mempersuasi Remaja di Kecamatan Karawaci, Kota Tangerang - Megi Primagara (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
Adolescents’ engagement in online gambling has emerged as a social communication phenomenon that continues to intensify alongside the expansion of digital media and networked interaction. This study aims to examine how online gambling agents employ Word Of Mouth (WOM) strategies to persuade adolescents through digital interpersonal communication and to explain how these strategies operate across the dimensions of talking, promoting, and recommending online gambling within youth communities in Karawaci District, Tangerang City. Using a qualitative case study approach, data were collected through in-depth interviews with one online gambling agent and three adolescent gamblers representing different levels of involvement. The findings indicate that online gambling agents act as central persuasive communication actors who actively construct interpersonal relationships via instant messaging platforms, transforming routine interaction into purposeful persuasive communication. The agents’ strategies reflect key elements of Cialdini’s Six Principles of Persuasion, particularly Reciprocity, Authority, Liking, and Social Proof, which are predominantly processed by adolescents through the peripheral route as outlined in the Elaboration Likelihood Model (ELM). Winning testimonials, gameplay recommendations, and betting patterns function as trust-building mechanisms that reduce perceived uncertainty within illegal online gambling practices. Furthermore, these WOM strategies diffuse through adolescents’ peer networks, fostering behavioral normalization and repeated engagement.